A nonlinear invariant attack on T-310 with the original Boolean function. Issue 2 (12th March 2021) - Courtois, Nicolas T.
Abstract: There are numerous results on nonlinear invariant attacks on T-310. In all such attacks found so far, both the Boolean functions and the cipher wiring were contrived and chosen by the attacker. In this article, we show how to construct an invariant attack with the original Boolean function that was used to encrypt government communications in the 1980s.